Performance of GNSS evil waveform detectors in the presence of multipath - Nunes, Fernando (2022)
The detection of evil waveforms (EWF) in GNSS signals is crucial to refrain from using anomalous signals in the PVT solution, which could degrade significantly its accuracy. The EWF detectors are, in general, based on the computation of the distortion of the code autocorrelation function. Thus, the multipath effect, an independent mechanism that also distorts the autocorrelation shape, can be incorrectly assumed by the EWF detector as the presence of EWF, leading to a major increase of the probability of false alarm. In the paper we analyze the robustness of the main EWF detectors and modulations to the presence of multipath.